Financial Performance and Stock Prices: Evidence from Firms Listed on the Jakarta Islamic Index - Via Muthmainnah Luthfi; Iwan Setiawan; Rina Nurmalina; Nafisah Ruhana (Indonesian Journal of Economics and Management, 2022)
This study aims to determine the effect of financial performance consisting of Return On Assets (ROA), Current Ratio (CR), Debt To Equity Ratio (DER), and Total Asset Turnover (TATO) on stock prices in companies listed in Jakarta Islamic Index period 2016-2020. The type of data used in this study is secondary data sourced from the company's financial statements, the official website of the Indonesian stock exchange, the website of each company, and the finance.yahoo.com website. The samples of this study are 9 companies that met the research criteria using purposive sampling method. The method used in this research is panel data regression analysis. The results of this study indicate that the ROA, CR, DER, and TATO variables simultaneously have a significant effect on the stock prices of companies listed on the Jakarta Islamic Index. While partially ROA has a positive and significant effect on stock prices. CR, DER, and TATO have a negative and significant effect on the stock prices of companies listed on the Jakarta Islamic Index.